Nove tujerodne rastlinojede žuželke v favni Slovenije - Seljak, Gabrijel (Acta entomologica slovenica (Ljubljana), 2017)
Five alien insects new to the fauna of Slovenia are recorded: Prociphilus (Meliarhizophagus) fraxinifolii (Riley 1879) Hemiptera: Aphididae, Cacopsylla fulguralis (Kuwayama 1908) Hemiptera: Psyllidae, Epitrix hirtipennis (Melsheimer 1847) Coleoptera: Chrysomelidae, Euxesta notata (Wiedemann 1830) and E. pechumani Curran 1938 Diptera: Ulidiidae. Diagnostic characteristics, bionomics, trophic features, distribution and potential economic as well as environmental threats of each species are briefly discussed. Each species is also photographically documented. A key for the identification of the alien Euxesta-species occurring in Europe is provided.
Keywords: alien insects; distribution; insects; prevalence; razširjenost; Slovenia; Slovenija; tujerodne žuželke; žuželke